EFEK PERUNDUNGAN MAYA TERHADAP HARGA DIRI DAN KECEMASAN REMAJA - Lailatun Nimah (Media Keperawatan:Politeknik Kesehatan Makassar, 2022)
The easier use of the internet increases the use of social media and the risk of exposure to cyberbullying among adolescents. The purpose of this study was to explain the relationship of cyberbullying to self-esteem and adolescent anxiety. This research method is cross sectional. The research population is adolescents in Surabaya, East Java. The sampling used was a purposive sampling of 120 adolescents. Demographic data obtained are age, gender and number of social media. The independent variable is cyber bullying while the dependent variable is self-esteem and anxiety. Statistical test used chi-square. The result of the p-value is 0.577 indicating that there is an insignificant relationship between cyberbullying and self-esteem. The p-value of 0.022 indicates that there is a significant relationship between cyberbullying and anxiety. Adolescents need to get assistance in the use of social media to reduce the negative impact of cyberbullying.